Unaccountable Form: Queer Failure and Jane Barker's Patchwork Method. - McGrath, Alice Tweedy (Eighteenth Century: Theory & Interpretation)
The article focuses on Jane Barker's innovative autobiographical fiction "A Patch-Work Screen for the Ladies" patchwork aesthetic as a methodological and formal model of queer failure. It mentions Barker's aesthetic of imperfection, linked to her socially marginal perspective and same-sex desire and advantage of the opportunities queer theory and patchwork conceit's aesthetic of lack and disruption. It also mentions heroic formulations of feminism.